Zapuszczanie korzeni na Zielonej Wyspie? Polacy w Irlandii w drugiej dekadzie po akcesji do UE - Weronika Kloc-Nowak (University of Warsaw, Centre of Migration Research (CMR), 2018)
– The paper describes the dynamics of Polish migration to Ireland, taking into account the situation of the Irish economy and changing demand for workers on the Irish labour market. It also presents the characteristics of Polish migrants in the light of Irish, Polish and European statistics. The main focus of the analysis is the situation of Polish nationals on the island according to the 2016 Irish census, also taking into consideration main trends of change in comparison with the previous censuses. Polish immigrants, who used to be rare in Ireland before 2004, have since become the largest group of non-Irish nationals, spread all over the country, stable in size and slowly ageing. In comparison with other immigrant groups in Ireland, Poles stand out with their large percentage of persons with tertiary education and at the same time - a growing share of those continuing education. The report points to such signs of Poles' developing ties with Ireland as the share of households with children, growing number of Polish-Irish citizens and home ownership. The types distinguished among Polish migrants and their long-term migratory strategies are discussed separately.
Keywords: 330; Ireland; Polish migrants; post-accession migration; census data